Hubungan Kerjasama Tim Dengan Missed Nursing Care Di Ruang Rawat Inap: Teamwork Relationship with Missed Nursing Care in the Inpatient Room - Razi, Fachrur (Chakra Brahmanda Lentera Institute, 2024)
Nurses are health workers who play an important role in health services in hospitals. One of the nurses' duties is to provide nursing care without being missed or delayed (missed nursing care). One of the causes of missed nursing care is ineffective teamwork. The purpose of this study was to determine the relationship between teamwork and missed nursing care in patient care at the hospital. This cross-sectional study involved 61 inpatient nurses. Data was collected using the MIISSCARE survey questionnaire to measure missed nursing care events and the nursing teamwork survey (NTS) to measure teamwork. The sampling technique used in this research is total sampling. Data were analyzed through descriptive statistics and Spearman's-Rho test with alpha <0.05. The results showed that the correlation test showed a p-value = 0.004 r = 0.359 that there was a relationship between teamwork and missed nursing care, the better the teamwork, the better low incidence of missed nursing care. Nurses are expected to be able to maintain good teamwork and be able to take part in nurse teamwork training.